Buyer groups as strategic commitments - James D. Dana (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
Buyer cooperatives, buyer alliances, and horizontal mergers are often perceived as attempts to increase buyer power. While prior theoretical and empirical work has emphasized that buyer size can increase buyer surplus, I show that even a small group of buyers with heterogeneous preferences can increase price competition among rival sellers by forming a buyer group and committing to buy exclusively from a single seller. The benefit to consumers from this commitment is the same as the benefit from committing to buy from the lowest price firm when they in fact prefer one firm's product. Finally, I suggest that buyer groups may be effective strategic commitments even when the agreement is potentially reversible.
Keywords: 330